2009
DOI: 10.1021/jp807277r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Boundary Dependent Errors in QM/MM Simulations

Abstract: Hybrid quantum mechanics/molecular mechanics (QM/MM) simulations provide a powerful tool for studying chemical reactions, especially in complex biochemical systems. In most works to date, the quantum region is kept fixed throughout the simulation and is defined in an ad hoc way based on chemical intuition and available computational resources. The simulation errors associated with a given choice of the quantum region are, however, rarely assessed in a systematic manner. Here we study the dependence of two rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 35 publications
3
103
1
Order By: Relevance
“…QTCP 0 in set 2). The reason why previous investigations have given better results with electrostatic embedding 15,19,22,23 is that the results depends on the tested system, i.e. the relative importance of polarisation and the junction errors, but also that we have in this investigation developed new variants of mechanical embedding (ME dir and ME scal ) that give the best results.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…QTCP 0 in set 2). The reason why previous investigations have given better results with electrostatic embedding 15,19,22,23 is that the results depends on the tested system, i.e. the relative importance of polarisation and the junction errors, but also that we have in this investigation developed new variants of mechanical embedding (ME dir and ME scal ) that give the best results.…”
Section: Discussionmentioning
confidence: 95%
“…This is appreciably more than in previous studies. 15,24,12,19,20,21,22,23 By systematically adding different components and corrections, we can estimate the size of the various terms and the accuracy of the various corrections. We have arrived at several interesting conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The resulting NBOs may then be categorized into chemically-intuitive Lewis-type bonding and lone pair orbitals, as well as their anti-bonding counterparts. Electronic delocalization from filled to vacant NBOs causes a variational lowering of the total energy, which can be estimated from second order perturbation theory (∆E (2) , see SI). This stabilization energy is strongly correlated with the strengths of hydrogen bonds in simple systems, 17,18 and we can therefore use it as a qualitative estimate of the importance of activesite residues in the catalytic rate enhancement in CM.…”
mentioning
confidence: 99%
“…A similar study was carried out by Solt et al 12 in a full QM/MM framework where they attempt to assess in a systematic manner simulation errors at the center of the QM region as a function of the size of that region. They showed that even with a full MM coupling, there are significant errors in the forces affecting atoms near the edge of the QM region By reducing the secondary subsystem to a simple electrostatic environment, the interaction between primary and secondary subsystems is greatly simplified.…”
Section: Introductionmentioning
confidence: 97%